Synthesis of New 5-Arylazo-3-Benzyl-2-Arylimino-4-Thiazolidinones - Singh, B.N. (Asian Journal of Chemistry, 2010)
A number of 5-arylazo-3-benzyl-2-arylimino-4-thiazolidinones have been synthesised by coupling 3-benzyl-2-arylimino-4-thiazolidinones with aryldiazonium chlorides. Structure of these compounds was supported by spectral studies.